Arrangement of the Rumah Lontiok Area as a Living Monument for Malay Traditional Architecture Tourism in Kampar Regency - Husaini, Muhd. Arief Al; Hidayat, Wahyu; Mashuri, Mashuri; Djuniati, Sri; Fikri, Asyrul; Mustaqimmah, Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Rumah Lontiok is a traditional Malay house in Kampar Regency. One of the Rumah Lontioks that exists as residences and tourist attractions is the Rumah Lontiok in Kampung Pulau Belimbing which is a hundred years old. However, currently, there is damage in the spatial layout of the Rumah Lontiok area which is characterized by not placing the building according to its original condition. This will eliminate the value of the cultural significance of the Rumah Lontiok area. The purpose of this writing is to obtain a conservation plan for the arrangement of the Rumah Lontiok area. The method used is qualitative descriptive. The author conducted an interview, excavated historical information, and observed the state of the Rumah Lontiok area. The results obtained are the concept of adaptive use in area conservation by restoring buildings to their original state and adding tourist facilities to support cultural tourism activities in the Rumah Loniok area.